(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
Continuity and discontinuity of functions is very important in mathematics. If a function is discontinuous at a point then it fails the definition of continuity of the function at that point and so the graph of the function has a break at that point. Such break of the graph of the function at that point may or may not be removed to make it continuous at that point. So we have different types of discontinuity of functions. I mention briefly about it below.